-
It should be 2x 3, one root is the cube root of 1-1 2, you can't type it out in this, and two are complex solutions, you can solve it yourself.
-
1) a=3, b=-6, c=1, so x=
i.e. x 1 =
3 ,x 2 =
2) Original = 9-16 (-8) + 1- 2
2 =9+2+1-3=9 ,4, Calculation: (1) Solve the quadratic equation with a clear solution: 3x 2 -6x+1=0 before the feastWalking stool.
2) (1 3 ) 2 -16÷(-2 ) 3 +(tan60° )0 -2 3 cos30° .
-
You are bright and respectful! Glad for your question! Lift aside.
Answer: 3x 1 6x is a quadratic equation.
Yours and likes are the greatest support for me! Break a leg! Thank you!
-
Solution: 6 (1-x) + 5 (x-2) = 2 (2x + 3), 6-6x + 5x-10 = 4x + 6, x - 4 = 4x + 6, 5x = -10, bury divination.
x=-2, the solution of the equation is envy.
x=-2。Laughing liquid shoot.
-
Solve the potato trillion liquid. 6(1-x)+5(x-2)=2(2x+3)6-6x+5x-10=4x+6
x-4=4x+6
5x=-10
x=-10 5=-2
-
x^3+6x^2+11x+6
x^3+5x^2+6x)+x^2+5x+6x(x^2+5x+6)+x^2+5x+6
x+1)(x^2+5x^+6)
x+1)(x+2)(x+3)
The excavation is carried out by the ridge next to the mountain x1=-1,x2=-2,x3=-3
-
2x+1)(x-3)=-6
Solution: 2x -5x-3 + 6 = 0
2x Yuanhao Shen socks - 5x+3=0
Hail 2x-3) (x-1) = 0
2x-3=0 x-1=0
x1=3/2 x2=1
-
Look at the right side as a whole.
Then move the item. (3x-2)(x+1)-(4-6x)=0, i.e., (3x-2)(x+1)+2(3x-2)=0 is refactored.
Get (3x-2)(x+3)=0
Solve x=2 3 or -3
The analytic expression of two circles, their intersection is the solution.
The equation is 2x 2 + 4x + k-1 = 0
Solution: 1) Discriminant = 16-8*(k-1) 0 >>>More
1)31a+5b=11 (1)
62a+15b=77 (2) >>>More
The first system of equations.
5x-6y=1 ① >>>More
I know: because p 2-p+>=0 is true. (as can be seen from p 2-p + > = 0). >>>More